2008
DOI: 10.2139/ssrn.1107959
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Value Creation: Evidence from Private Equity

Abstract: We examine deal-level data on private equity transactions in the UK initiated during the period 1996 to 2004 by mature private equity houses. We un-lever the deal-level equity return and adjust for (un-levered) return to quoted peers to extract a measure of "alpha" or abnormal performance of the deal. The alpha is significantly positive on average and robust during sector downturns. In the cross-section of deals, higher alpha is related to greater improvement in EBITDA to Sales ratio (margin) and greater growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
132
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(150 citation statements)
references
References 5 publications
18
132
0
Order By: Relevance
“…In particular, median sales increase by about 50%, EBIT and EBITDA increase twofold, and cash flows increase by three times, this time with significance both in means and medians. These results are strongly supportive of the arguments in Acharya et al (), Boucly et al (), and Kaplan and Stromberg () that PE investors stimulate growth in target companies through superior managerial skills.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…In particular, median sales increase by about 50%, EBIT and EBITDA increase twofold, and cash flows increase by three times, this time with significance both in means and medians. These results are strongly supportive of the arguments in Acharya et al (), Boucly et al (), and Kaplan and Stromberg () that PE investors stimulate growth in target companies through superior managerial skills.…”
Section: Methodssupporting
confidence: 88%
“…In any of these cases, I should observe significant differences in the fund/management company characteristics. In addition, the performance of the target companies is certainly associated with some superior skills by the PE sponsor as demonstrated in Acharya et al (), Boucly et al (), and Kaplan and Stromberg (). Skills are most likely to build up over time.…”
Section: The Operating Performance Of Target Companiesmentioning
confidence: 98%
“…Importantly, either the level of ex ante risk or the expected value of a target firm may correlate with the change in the target's market value or with policymakers' effort to enact UTSA—for instance, to protect riskier or more valuable businesses better. To account for such potential confounders, we reestimate the baseline specifications, while also matching the treatment and control firms on the basis of ex ante investment size, which proxies for the target's ex ante value, and industry resource–value uncertainty, which proxies for the target's business riskiness (Acharya et al , ; Castellaneta and Zollo, ; Shepherd, ). We used a coarsened exact matching (CEM) approach as developed by Iacus, King, and Porro () to perform a match between treatment and control.…”
Section: Resultsmentioning
confidence: 99%
“…The findings within are consistent with Acharya et al . () who found that substantial private equity postacquisition value comes from improving operating performance and human skills. The results highlight that the role of current‐day private equity differs to the financial engineering emphasis of earlier leveraged buyouts of the 80s.…”
Section: Resultsmentioning
confidence: 99%
“…Acharya et al . () found that nearly one‐third of private equity's postacquisition value came from improving operating performance and human skills. An alternative way to interpret this finding is that public governance has, in certain settings, sufficient levels of inefficiency to attract private equity sponsors.…”
Section: Introductionmentioning
confidence: 99%